Cardiovascular Disease Risk Awareness and Its Association With Preventive Health Behaviors: Evidence From a Sample of Canadian Workplaces. Issue 5 (May 2016) - Jacobs, Josephine C.; Burke, Shauna; Rouse, Michael; Sarma, Sisira; Zaric, Greg
Abstract : Objective: The aim of this study was to determine Canadian workers' level of awareness about their cardiovascular disease (CVD) risk factors and the association between CVD risk awareness and health behaviors. Methods: We used cross-sectional data to compare awareness of CVD risk factors with biometric measures from a workplace screening clinic ( n  = 320). We assessed the association between risk factor awareness and self-reported health behaviors using logistic regression analyses. Results: Overall, 39.5% of workers did not know at least one of their CVD risk factors. These individuals were less likely to meet recommended physical activity levels and to consume three daily servings of fruits and vegetables, and more likely to report weekly fast food consumption. Conclusions: This study highlights a lack of awareness about cholesterol levels and demonstrates a negative association between low CVD awareness and preventive health behaviors.